2014
DOI: 10.1039/c4cc01950d
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-fixation catalyst based on graphene: every part counts

Abstract: The catalytic profile and function of each component of a molybdenum-graphene based catalyst (Mo/N-doped graphene) for nitrogen fixation, which combines the merits of these two components, is evaluated computationally. The Mo/N part acts as an active centre for N2 bond breaking and the graphene part works as an electron transmitter and electron reservoir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 27 publications
1
79
0
Order By: Relevance
“…Charge population analysis then revealed that the graphene serves as the electron reservoir, while the FeN 3 acts as the active center and the transmitter for electron transfer. Similar computational results have also been reported for Mo/N‐doped graphene catalyst, in which the MoN 3 moiety acts as the active center for N 2 bond breaking and the graphene serves as the electron transmitter and electron reservoir for protonation and reduction (Figure b) …”
Section: Nitrogen Fixation At Atomic‐scale Active Sitessupporting
confidence: 81%
See 1 more Smart Citation
“…Charge population analysis then revealed that the graphene serves as the electron reservoir, while the FeN 3 acts as the active center and the transmitter for electron transfer. Similar computational results have also been reported for Mo/N‐doped graphene catalyst, in which the MoN 3 moiety acts as the active center for N 2 bond breaking and the graphene serves as the electron transmitter and electron reservoir for protonation and reduction (Figure b) …”
Section: Nitrogen Fixation At Atomic‐scale Active Sitessupporting
confidence: 81%
“…b) Schematic illustration of NRR on the Mo/N‐doped graphene catalyst. Reproduced with permission . Copyright 2014, The Royal Society of Chemistry.…”
Section: Nitrogen Fixation At Atomic‐scale Active Sitesmentioning
confidence: 99%
“…Based on the existing experience, Tian et al explored the possible reaction mechanism of N fixation by SA Mo–N–C catalyst through theoretical calculation, molecular orbital theory and particle analysis. It is found that the enzymatic route is beneficial in energy for the simultaneous bonding of two N atoms to the Mo atom, which is more feasible than the Schrock path ( Figure ) …”
Section: Theoretical Calculations For Nonprecious Metal Single Atomicmentioning
confidence: 99%
“…Aside from direct utilization as electrocatalysts, carbon materials are extensively used as catalyst support. Experimental evidence has confirmed that defects or doping heteroatoms in carbon materials are necessary for metal loading . Metal‐based catalysts including metals/alloys, metal oxides, nitrides, and chalcogenides are effective in electrocatalysis .…”
Section: Carbon Materialsmentioning
confidence: 99%